CFD analysis of flow induced vibration of cylinders and offshore structures - Isaac Mark Joseph Manasseh (2017)
Flow induced vibration is one of the major contributors to reduction in fatigue life of offshore structures. The two phenomena associated with fluid-structure interaction are: The vortex Induced Vibration, observed in structures with high aspect ratio like the risers and mooring systems; the Vortex Induced Motion of offshore platforms with low aspect ratio. A high fidelity fluid dynamics simulation is required to study the above phenomena and the corresponding data is recommended for the manufacture of structures which are not susceptible to Flow Induced Vibrations. kOmegaSST and kEpsilon employing RANS have proven to be reliable turbulence models to calculate hydrodynamic forces. The objective of the thesis is firstly, to investigate the effects of flow around cylinders at various Reynolds numbers and secondly, to propose a universal methodology to capture the VIM phenomenon. In this thesis the OpenFOAM software's groundwork is investigated concerning its capability to perform transient simulations. The simulations for cylinders were run at various flow regimes and the results were found to be satisfactory. The force coefficient- Reynolds number relationship have good conformity with other experimental results. The snappyHexMesh utility has proven to generate converged results for complex grids with low values of dimensionless wall distance y+. The main recommendation from the present work is to employ OpenFOAM's mesh utility for meshing complex offshore models and transient simulation capabilities for predicting hydrodynamic forces